Improved procedural workflow for catheter ablation of paroxysmal AF with high‐density mapping system and advanced technology: Rationale and study design of a multicenter international study. Issue 6 (21st April 2022) - Solimene, Francesco; Stabile, Giuseppe; Ramos, Pablo; Segreti, Luca; Cauti, Filippo Maria; De Sanctis, Valerio; Maggio, Ruggero; Ramos‐Maqueda, Javier; Mont, Lluis; Schillaci, Vincenzo; Malacrida, Maurizio; Garcia‐Bolao, Ignacio
Abstract: Background: The antral region of pulmonary veins (PV)s seems to play a key role in a strategy aimed at preventing atrial fibrillation (AF) recurrence. Particularly, low‐voltage activity in tissue such as the PV antra and residual potential within the antral scar likely represent vulnerabilities in antral lesion sets, and ablation of these targets seems to improve freedom from AF. The aim of this study is to validate a structured application of an approach that includes the complete abolition of any antral potential achieving electrical quiescence in antral regions. Methods: The improveD procEdural workfLow for cathETEr ablation of paroxysmal AF with high density mapping system and advanced technology (DELETE AF) study is a prospective, single‐arm, international post‐market cohort study designed to demonstrate a low rate of clinical atrial arrhythmias recurrence with an improved procedural workflow for catheter ablation of paroxysmal AF, using the most advanced point‐by‐point RF ablation technology in a multicenter setting. About 300 consecutive patients with standard indications for AF ablation will be enrolled in this study. Post‐ablation, all patients will be monitored with ambulatory event monitoring, starting within 30 days post‐ablation to proactively detect and manage any recurrences within the 90‐day blanking period, as well as Holter monitoring at 3, 6, 9, and 12 months post‐ablation. Healthcare resource utilization, clinical data, complications, patients' medical complaints related to the ablation procedure and patient's reported outcome measures will be prospectively traced and evaluated. Discussion: The DELETE AF trial will provide additional knowledge on long‐term outcome following a structured ablation workflow, with high density mapping, advanced algorithms and local impedance technology, in an international multicentric fashion. DELETE AF is registered at ClinicalTrials.gov (NCT05005143).